2021
DOI: 10.1002/bkcs.12221
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Decarboxylative Homodimerization of Propiolic Acids: Synthesis of 1,3‐Enynes

Abstract: The 1,3‐enyne product was obtained as a result of a decarboxylative homodimerization reaction when a variety aryl propiolic acids were reacted in the presence of Pd(TFA)2/i‐PrPPh2 and K2CO3. It was found that aryl propiolic acids bearing an electrondonating substituent provided the desired product; however, aryl propiolic acids an bearing electron‐withdrawing substituent did not give the desired product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Subsequently, the strategy was extended to provide gem -1,3-enynes 185 via a twofold decarboxylative homodimerization process of alkynoic acids (Scheme 59). 76…”
Section: Transition Metal Catalyzed Decarboxylative Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the strategy was extended to provide gem -1,3-enynes 185 via a twofold decarboxylative homodimerization process of alkynoic acids (Scheme 59). 76…”
Section: Transition Metal Catalyzed Decarboxylative Transformationsmentioning
confidence: 99%
“…Subsequently, the strategy was extended to provide gem-1,3-enynes 185 via a twofold decarboxylative homodimerization process of alkynoic acids (Scheme 59). 76 Xie et al reported an interesting approach for the synthesis of 1,4-enyne 188 motifs in high efficiency via the decarboxylative cross-coupling of alkynoic acids with allylic alcohols 186 or 187 (Scheme 60). 77 The reaction proceeds via the calciumpromoted dehydroxylation of allylic alcohols (C-OH cleavage) linked with consecutive decarboxylation and palladium-catalyzed allyl-alkynyl coupling processes.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%